How CCP Shanghai Manages Diversity through Strategic Human Resource Management - Sindri Sigurður Jónsson 1996- (2018)
This thesis aims to examine strategic human resource management and how it can be configured to manage diversity in a transnational company. Specifically, CCP’s Shanghai office was taken as an example because it is an Icelandic company with a branch located in China, which has a diverse workforce. In order gain a better understanding of the underlying cultural values of both countries, Iceland and China were compared via Hofstede’s cultural dimensions. Those cultural values serve as a foundation towards interpreting how employees in the Chinese affiliate might perceive HRM activities differently than in the parent enterprise. A four-step process towards managing diversity was formulated by the researcher to serve as a theoretical framework for judging the performance of CCP Shanghai’s strategic HRM activities. An in-depth qualitative interview was subsequently conducted with CCP Shanghai’s HR Director Helen Hu. The information gathered from previous research and the findings of the qualitative interview were compared using the diversity management framework to gauge where CCP Shanghai excels and where they can improve.